2018
DOI: 10.1111/jbi.13371
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal cladoceran (Branchiopoda) responses to climate change and UV radiation in subarctic ecotonal lakes

Abstract: Aim To understand modern and past aquatic community responses to climate‐induced shifts in productivity and ultraviolet radiation (UV) exposure. Location Tree line ecotone from north boreal forest to subarctic tundra in northeastern Finnish Lapland. Taxon Cladocera (Crustacea: Branchiopoda). Methods Thirty‐one small and shallow lakes were examined for summer epilimnetic communities (SEC) and surface sediment fossil integrative communities (FIC) of Cladocera for species distribution and their environmental corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 56 publications
(98 reference statements)
1
23
1
Order By: Relevance
“…Empirical evidence to test this hypothesis is currently lacking, however. Surface UV-B proxy reconstructions based on the abundance of photoprotective pigments in fossil cladocera (water flea) carapaces in arctic and subarctic lakes (Nevalainen et al, 2015(Nevalainen et al, , 2016(Nevalainen et al, , 2018) demonstrated a positive correlation between surface UV-B and solar activity over the last millennium, which is the opposite pattern to that predicted by Rozema et al (2002).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Empirical evidence to test this hypothesis is currently lacking, however. Surface UV-B proxy reconstructions based on the abundance of photoprotective pigments in fossil cladocera (water flea) carapaces in arctic and subarctic lakes (Nevalainen et al, 2015(Nevalainen et al, , 2016(Nevalainen et al, , 2018) demonstrated a positive correlation between surface UV-B and solar activity over the last millennium, which is the opposite pattern to that predicted by Rozema et al (2002).…”
Section: Introductionmentioning
confidence: 87%
“…However, UV-B proxies based on aquatic organisms such as cladocerans are influenced by water transparency as well as ambient UV-B, and so relate at least in part to local climatic and vegetation conditions and anthropogenic land use changes (Nevalainen et al, 2015(Nevalainen et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…However, the latter ABS UV peaks were likely related to a more transparent water column during the LIA, related to constrained organic matter flux from the catchment and reduced in-lake production driven by longer ice-cover period. A similar pattern of increased aquatic UV exposure during the LIA has occurred in lakes of northern and eastern Finland and in the Alps [30,53]. The pre MCA period at the middle of the first millennium of the Common Era has been characterized to be hydroclimatically dry in Fennoscandia.…”
Section: Paleo-opticsmentioning
confidence: 64%
“…Although solar forcing interacted partly in cladoceran assemblage succession, SSN reconstruction explaining 12% of the species variation (Figure 3), it did not have substantial association with the current ABS UV record (Figure 4). In an adjacent lake, which differed from Loažžejávri by its location in the mountain birch woodland at a lower altitude, millennial variation in ABS UV was in clear connection with solar intensity [13,53]. In Loažžejávri, highest carapace ABS UV was recorded in the early core (~300 and 500 C.E.)…”
Section: Paleo-opticsmentioning
confidence: 86%
See 1 more Smart Citation